SINTESIS KITOSAN DARI LIMBAH CANGKANG KEPITINGSEBAGAI PENJERNIH AIR - Alawiyah, Tuty; Hadi, Taufikul (Jurnal Ilmiah IKIP Mataram, 2018)
In this research, the synthesis of chitosan from crab shell waste can then be applied for water purification. Crab shells have a chitin compound of around 70%. Chitin can be deacacylated into a compound called chitosan. The process of obtaining chitin substances can be done in three stages, namely demineralization, deproteination, and depigmentation, while chitosan is obtained from the deacetylation process of chitin with a high concentration alkaline solution. In this study the demineralization stage was carried out using 1N HCl then the deproteination stage was carried out using a base solution with a concentration of 3.5% at 65 Â° C for 2 hours. Then the chitin deacetylation into chitosan was carried out using a high concentration base solution of 50% at 100 Â° C for 6 hours. The results obtained were characterized by using an Infrared Spectrophotometer to determine the degree of deacetylation with a wavelength of 4000 cm-1 to 450 cm-1